"Outta my way!" Individual and environmental correlates of interactions between pedestrians and vehicles during street crossings. (July 2017) - Cloutier, Marie-Soleil; Lachapelle, Ugo; d'Amours-Ouellet, Andrée-Anne; Bergeron, Jacques; Lord, Sébastien; Torres, Juan
Highlights: A naturalistic observation data collection was put in place to explore interaction occurrence between pedestrians and other road users. Child pedestrians observed near elementary schools were involved in less interactions than other age groups. Pedestrians in the 65–79 year-old age group were the ones with the highest proportion of interactions. Slower walking speed was associated to a greater probability of interaction. The presence of an arterial road at the crossing site intersection was strongly associated to a greater probability of interaction. Abstract: Because pedestrian crash rates remain lower than other collision types, surrogate measures such as traffic interactions are now used in road safety research to complement crash history. Using naturalistic data collection, we sought to assess 1) the likelihood of occurrence of interactions between pedestrians and vehicles based on individual and crossing characteristics; and 2) differences in interaction characteristics between children, adult and senior pedestrians. Observations of pedestrian crossing behaviours ( n  = 4687) were recorded at 278 crossings. For recorded interactions ( n  = 843), information was collected to characterize the behaviours of involved parties. A mixed-effect logit regression model was performed to assess the factors associated with interactions. Chi-square tests evaluated differences between age groups and characteristics of observed interactions. Older adults were those more likely to be involved in an interaction event. Bicycle paths, different crossing surface material and one-way streets were significantly associated with fewer interactions with vehicles, while parked vehicles nearby and crossings on arterial roads were significantly associated with more interactions. Children and the elderly (80 years of age or more) did have distinct patterns of interaction, with more careful drivers/cyclists behaviours being observed towards children and lesser regulation compliance towards the elderly. Given the growing emphasis and adoption of active transportation in many cities, the number of interactions between pedestrians and vehicles during street crossings is likely to increase. Educating drivers and pedestrians to respect each other's space requires an understanding of where, between whom, and under what circumstances interactions occur. Such an approach can also help identify which engineering and enforcement programs are needed to ensure safe pedestrian crossings since interactions can be good markers of uncomfortable crossing situations that may deter walking and lead to more collisions.